Screening of coformers for quercetin cocrystals through mechanochemical methods - Souza, Fayene Zeferino Ribeiro de; Almeida, Amanda Cosmo de; Ferreira, Patrícia Osorio; Fernandes, Richard Perosa; Caires, Flávio Junior (Eclética Química, 2022)
Quercetin (QUE) is a nutraceutical compound that exhibits pharmacological properties such as antioxidant, cardioprotective, anti-ulcer, and anti-inflammatory effects. Although QUE is well-known for its benefits, its efficacy is limited due to low solubility. Thus, cocrystallization acts as an interesting approach to improve the solubility—among other properties—of this compound. In this work, cocrystallization screening was applied through neat grinding (NG) and liquid-assisted grinding (LAG), in which QUE and four cocrystal formers (benzamide, picolinamide, isonicotinamide, and pyrazinoic acid) were tested. The precursors and QUE-coformer systems were characterized using thermoanalytical techniques (TG-DTA), X-ray powder diffraction (XRPD), and Fourier transform infrared (FTIR) spectroscopy. The results showed the formation of QUE cocrystals with picolinamide and isonicotinamide coformers in a 1:1 stoichiometric ratio. Furthermore, although coformers are isomers, spectroscopic and thermal data suggest that the supramolecular synthons involved in cocrystallization are different.